FOREIGN POLICY STRATEGY OF THE REPUBLIC OF SINGAPORE IN THE AFRICAN REGION (Вісник: Міжнародні відносини, 2021)
The article describes the development of the strategy of advancing the interests of the Republic of Singapore in the African region. Based on the analysis of the activities of Enterprise Singapore, the author examines the specific measures taken by the Government to establish partnerships with countries of the region. Given the high investment opportunities of the Republic of Singapore, particular attention is paid to cooperation in trade and economy and to development of collaboration in regular Africa Singapore Business forums.
Keywords: Republic of Singapore, foreign policy strategy, digital economy, responsible investment, Africa Singapore Business Forum, Asian hub